Simulação numérica do desempenho térmico de alvenaria construída com blocos de concreto - Rodrigues, Marília Guimarães (2022)
The concern with environmental sustainability applied to civil construction, especially given the need for non-depletion of natural resources and energy efficiency, demonstrates the importance of thermal performance in buildings in accordance with performance standards, which aims to verify compliance with criteria minimums concerning thermophysical characteristics for closure systems. The new revision NBR 15575 (ABNT, 2021) establishes criteria for evaluating the thermal performance of the building and the results allow for an adjustment in the planning and preparation of projects, changing the building components or the architectural model of the building in order to seek better thermal performance for the building. The objective of the work was to improve the structural concrete block from the standard unit of the family 39, aiming at improving the thermal performance of the building through its specification. After studies of form and function, the prototype was named as DT 39 Block. As a methodology, an exploratory research was carried out. The evaluation was performed by calculating the thermal transmittance and thermal capacity of the building envelope and compression tests of the unit and prism. Computational simulations were performed using the EnergyPlus program, which allowed testing the weather conditions on the building and determining its thermal behavior before the insertion of the new DT 39 Block in different design configurations. The results obtained were compared and analyzed according to the requirements of NBR 15575-1 (ABNT, 2021), which made it possible to generate comparative graphs between the buildings simulated with the standard block and with the new developed block (DT 39). Through the results of the simulations, it was possible to evaluate that with the modification in the geometry of the concrete block it was possible to improve the thermal performance of the simulated buildings, that is, with the specification of the new block in the building, whether applied to a wall or to all walls of the building, it was possible to change their thermal performance level, leaving the minimum level of thermal performance, to the intermediate level. In other words, when both buildings were inserted in the DT 39 Block, they improved the comfort percentage of the simulated buildings and reduced their thermal load.